Flame quenching by crimped ribbon flame arrestor: A brief review. Issue 1 (9th August 2018) - Wang, Lu‐Qing; Ma, Hong‐Hao; Shen, Zhao‐Wu; Chen, Dai‐Guo
Abstract : Accidental explosions in gas/oil pipelines remain one major concern in process industries. The crimped ribbon flame arrestor is an effective device to prevent flame propagation. This review summarizes existing knowledge on the quenching of flame of different regimes in narrow channels and crimped ribbon flame arrestors. The influences of various parameters (e.g., arrestor element thickness, expansion ratio, system pressure) on the performance of crimped ribbon flame arrestors are discussed. The presented discussions give a better understanding on the considerations which must be taken into account to quench an explosion successfully. Other scenarios, such as quenching of two‐phase vapor‐liquid explosions and overdriven detonations should be got further attention. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 27–41, 2019